Estudio de factibilidad para exportar uchuva deshidratada hacia el mercado de Berlín – Alemania (2023)
This study analyzes the Colombian fruit and vegetable sector from the production of uchuva, as it is one of the products with the greatest export potential in the country, non-traditional raw materials are in the process of transformation, and the exploitation of the geographical potential of the Colombian territory is also manifested as a competitive advantage in the production of tropical fruits.